The cost of free shipping : Amazon in the global economy - Alimahomed-Wilson, Jake; Reese, Ellen, 1969- (Wildcat (Pluto Press), 2020)
'Amazon Capitalism' grows ever stronger. This book provides the answers on how to fight the company's terrifying omnipotence.